Donor Advised Funds & Delay: An Intergenerational Justice Solution? - Murray Ian (Nonprofit Policy Forum, 2023)
Much writing on Donor Advised Funds (DAFs) relates to whether they ‘unduly’ delay the direct application of donated funds to achieve public benefit. However, the discussion rarely touches on a normative basis for determining what is ‘undue’ or that can be used to shape potential reforms, which are typically framed with reference to a private foundation payout rate or time limit for expending contributions. Research on charity accumulation conducted across the United States, United Kingdom, Canada, Australia and New Zealand, suggests that the normative principle of intergenerational justice is helpful for grounding such discussions (Murray, I. 2021. Charity Law and Accumulation: Maintaining an Intergenerational Balance. Cambridge: Cambridge University Press). This article considers intergenerational justice in the context of DAFs and considers whether the principle can be implemented in ways that support DAF sponsor independence and flexibility. One way that this could be achieved is by imposing (or enforcing existing) procedural obligations on decision-makers to give genuine consideration to intergenerational justice when making decisions about how much to spend and retain.